2007
DOI: 10.1128/jcm.00133-07
|View full text |Cite
|
Sign up to set email alerts
|

Organisms Designated as Nocardia asteroides Drug Pattern Type VI Are Members of the Species Nocardia cyriacigeorgica

Abstract: Nocardia cyriacigeorgica has recently been described as an “emerging” pathogen. However, DNA-DNA hybridization results confirm that Nocardia asteroides drug pattern type VI, which has long been recognized as a common and significant pathogen in the United States, belongs to the species N. cyriacigeorgica .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Additional sequences should either reassign these isolates to type strain-defined species clusters or prompt the characterization of new species. The species or subspecies status of the three subclusters of N. cyriacigeorgica would benefit from further taxonomic investigation, especially considering its importance as a human pathogen (9,39 new species, provided that they fail to cluster with additional type strains when they are incorporated into the analysis. In all cases, novel species discovery must be supported by MLSA as well as DDH data, extensive biochemical and phenotypic characterizations, and perhaps ecological distinction (12,13,20,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Additional sequences should either reassign these isolates to type strain-defined species clusters or prompt the characterization of new species. The species or subspecies status of the three subclusters of N. cyriacigeorgica would benefit from further taxonomic investigation, especially considering its importance as a human pathogen (9,39 new species, provided that they fail to cluster with additional type strains when they are incorporated into the analysis. In all cases, novel species discovery must be supported by MLSA as well as DDH data, extensive biochemical and phenotypic characterizations, and perhaps ecological distinction (12,13,20,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…This is partly due to the discrepancy between the manufacturers' recommendations and the findings of Biehle et al, who demonstrated an ϳ1-log 10 -dilution-lower inoculum size when using the recommended 0.5 MacFarland suspension (2). Major taxonomic revisions have occurred within the last 10 years, further complicating the comparison of studies (7,11,12,21). With potentially important clinical and epidemiological differences between species, it is important to identify isolates to the species level as accurately and rapidly as possible.…”
mentioning
confidence: 98%
“…However, Conville and Witebsky (17) confirmed that N. asteroides drug pattern VI, which since its description in 1988 has been considered the most commonly encountered group of Nocardia isolates recovered from clinical samples, is identical by DNA-DNA hybridization to the species N. cyriacigeorgica and, as such, should not be considered a "new or emerging species of Nocardia. "…”
Section: The "N Asteroides" Storymentioning
confidence: 85%